Augmented Reality Learning Materials for Motion Picture Making Subject - Hirnanda Dimas Pradana; Dedi Kuswandi; Sulton Sulton (Pascasarjana UM, 2018)
Abstract: Learning materials is one of the important components of learning. Learning materials based on Augmented reality is capable of accommodating the needs of learners. Augmented reality intends to insert virtual objects into the real environment. In recent activity, learning materials are still using conventional media such as presentation slides and the internet. Consequently, students do not obtain appropriate material for certain learning. Learning materials assisted by augmented reality can be a solution for students in understanding moving pictures. The development model used was the Lee & Owens model. It produces valid and effective learning material products with augmented reality.Key Words: learning materials, augmented reality, motion picture, multimedia, vocational high schoolAbstrak: Bahan ajar merupakan salah satu komponen penting dalam pembelajaran. Bahan ajar yang baik ialah bahan ajar yang mampu mengakomodir kebutuhan pebelajar. Pada sekolah yang diteliti, bahan ajar yang ada masih menggunakan media slide presentasi dan bahan ajar diambil dari internet, sehingga pebelajar mengalami kesulitan jika sudah berada di luar kelas. Selain itu, pebelajar mengalami kesulitan belajar materi yang sesuai dengan kompetensi yang dibutuhkan. Bahan ajar berbantuan augmented reality dapat menjadi solusi bagi pebelajar dalam memahami pengambilan gambar bergerak. Model pengembangan yang digunakan ialah model Lee & Owens. Penelitian menghasilkan produk bahan ajar berbantuan augmented reality yang valid dan efektif.Kata kunci: bahan ajar, augmented reality, gambar bergerak, multimedia, sekolah menengah kejuruan